UPAYA PENINGKATAN PEREKONOMIAN MASYARAKAT MELALUI BUDIDAYA IKAN NILA DI DANAU MANINJAU NAGARI TANJUNG SANI KABUPATEN AGAM - Ayuni Dwi Putri; Khadijah Nurani (Jurnal Ekonomi dan Bisnis, 2023)
This thesis is entitled, "Efforts to Increase the Community's Economy Through Tilapia Cultivation in Lake Maninjau Nagari Tanjung Sani, Agam Regency". Compiled by Ayuni Dwi Putri with NIM 3219300. Student Thesis of the Faculty of Islamic Economics and Business, Islamic Economics Study Program, State Islamic University (UIN) Sjech M. Djamil Djambek Bukitinggi. The background of this research is the lack of maximum yields of tilapia in the Nagari Tanjung Sani community and tilapia cultivation has not been able to reach the target they want to achieve. This study describes efforts to cultivate tilapia as a source of community income and explains what constraints are often faced by these communities. This research is a type of field research (freld research) which is qualitative in nature which produces descriptive data in the form of spoken and written words and observed behavior, with a number of informants who were interviewed by ten people. From the results of research conducted in Nagari Tanjung Sani, Tanjung Raya District, Agam Regency, it can be stated that the efforts used to increase people's income in the tilapia cultivation business in the community are to increase the production of tilapia aquaculture to increase people's income, make new innovations in terms of tilapia cultivation. The obstacles experienced by the community are the lack of understanding of human resources that carry out tilapia cultivation, as well as limited capital in developing a wider business, but they are still enthusiastic in developing tilapia cultivation business.